Ultra-sensitive flexible sandwich structural strain sensors based on a silver nanowire supported PDMS/PVDF electrospun membrane substrate. Issue 8 (3rd February 2021) - Yang, Zhenhua; Wu, Zijian; Jiang, Dawei; Wei, Renbo; Mai, Xianmin; Pan, Duo; Vupputuri, Sravanthi; Weng, Ling; Naik, Nithesh; Guo, Zhanhu
Abstract : Flexible sandwich structural strain sensors based on silver nanowire supported PDMS/PVDF electrospun membrane substrates exhibit a gauge factor of 654.5. Abstract : Elastomers embedded with a layer of conductive nanoparticles in the form of a sandwich structure are one of the most popular means to achieve high performance flexible sensors. However, owing to the lack of interaction between adjacent nanoparticles, the number of detached conductive nanoparticles increases when repeated strain/release cycles are applied, thereby causing the electrical resistance of the conductive layer to increase irreversibly. In this work, we report a high-performance piezoresistive sensor based on a novel sandwich structure composite to address this problem. Polydimethylsiloxane (PDMS) and poly(vinylidene fluoride) (PVDF) were blended to prepare a highly elastic PDMS/PVDF electrospun membrane, then silver nanowire (AgNW) suspensions were directly pumped into the electrospun membranes through a simple filtration process to prepare a conductive layer in a sandwich structure. Accordingly, this hybrid conductive layer was embedded into two layers of PDMS to prepare sandwich structure sensors (PPAP). The PDMS/PVDF electrospun membrane possessed excellent stretch–recovery capability and better interfacial compatibility. More importantly, the porous structure of the membrane effectively restricted the movement range of adjacent nanoparticles and formed a more stable conductive network structure. The maximum gauge factor (GF) of 654.5 of the sensor with a conductive layer structure is significantly higher than those of most reported sensors with a similar sandwich structure. The introduced conductive interlayer is a critical factor to improve the structure stability and dispersion uniformity of the AgNW network while ensuring the interfacial compatibility and elastic matching between the sensing and PDMS layers, which directly improve the durability and hysteresis. The microcrack structure observed in the sensing layer of the PPAP sensor was one of the main reasons for achieving an ultra-high sensitivity of the PPAP sensor. In the end, the wrinkled morphologies are formed after pre-stretching, and the wrinkled sensor exhibits a GF as high as 3058. This study justifies that the sandwich structure exhibits potential for strain sensing applications.